Development of Malaysian river stability index by incorporating morphological assessment in normal flow conditions - Haron, Nor Azidawati (2021)
Various river-related issues continue to escalate throughout the year. The situation is exacerbated further when river stability assessment is extremely limited. Numerous rivers are unable to maintain an equilibrium flow regime, and unintentionally, Malaysia's rivers that have not been encroached upon have suffered due to the country's development. During development, too much suspended and bed sediment enters the river channel, and the channel undergoes excessive geomorphic responses, jeopardising the river's stability. Malaysia's Department of Irrigation and Drainage (DID) currently uses hydrodynamic modelling analysis to manage various river issues, including river pollution, erosion, and sedimentation. In the evaluation, the current methods were lacking in determining the river stability index. It is therefore essential to provide immediate attention to the development of the Malaysian River Stability Index (MRSI), which incorporates river morphological assessment in normal flow conditions as the primary goal of this research. Through tools and readily available results, MRSI enhances the evaluation of river stability. It is crucial to classify the selected rivers' physical and hydraulic properties, assess the river's flow regime, equilibrium hydraulics geometry, and geomorphic responses that changed the river's morphology, and develop MRSI's river stability incorporate a morphological assessment. The researcher carried out the research in five stages. In stage I, the site was chosen using the REFCON approach. The selected rivers were Lepoh, Congkak, Sekayu and Rasau River. In stage II, the extensive river measurement and laboratory work were completed. The raw data was then analysed in stage III to obtain hydraulic information. The physical and hydraulic elements of river morphology were identified in stage IV, where four forms of morphology have been studied: cascade, pool, step-pool, and plain bed. The flow regime and equilibrium hydraulics geometry analysis were then performed by charting the log-log graph as a power function of flow discharge and velocity, width, and depth. The geomorphic response of each river crosssection has been identified through a calculation based on the geomorphic response formula. Three steps are involved in stage V: (i) determining the index value for each sub-index (indicator) and selective criteria (optional criteria) of MRSI using the Analytical Hierarchical Process (AHP); (ii) developing the MRSI scoring system using the Likert Scale; and (iii) developing MRSI tools named SMRSI using the Visual Basic application. AHP was the most suitable method to disentangle the inclination evaluations among the choices of index stability indicators using pairwise comparison. It was determined through AHP consistency that the highest index value indicates the most crucial indicator of river stability. The MRSI index, based on the Likert scale, indicates the degree of river stability, which consists of excellent (MRSI score 47–55), good (37–47), satisfactory (27–37), poor (17–27) and very poor (2–17). Several calibrations were performed by comparing the MRSI to the existing stability assessment. A Cronbach’s Alpha value of 0.81 indicates that the stability assessment's consistency was robust. The MRSI and the existing stability index were equivalents.